Effects of H2O, SO2, and NO on Homogeneous Hg Oxidation by Cl2 - Agarwal, Hans; Stenger, Harvey G; Wu, Song; Fan, Zhen (Energy & fuels, 2006)
Several researchers have determined that water (H2O) and sulfur dioxide (SO2) in a flue gas stream have an impact on the amount of elemental mercury (Hg0) that is homogeneously oxidized by a chlorine-containing species. Generally, it is concluded that H2O inhibits Hg oxidation by chlorine (Cl2). However, doubt remains as to whether SO2 promotes or inhibits Hg oxidation. Further, most published results seem to indicate that nitric oxide (NO) does not have a significant impact on Hg oxidation. This paper will present data taken in a laboratory-scale apparatus designed to test these observations. In this work, Cl2 is intentionally added to a synthetic flue gas stream containing known amounts of elemental mercury. This gas blend is similar to a flue gas obtained by burning Powder River Basin coal in a pulverized coal fired power plant and is subject to a time−temperature profile similar to a power plant. The results obtained show that H2O, SO2, and NO all have an inhibitory effect on the homogeneous oxidation of Hg by Cl2. Further, the presence of H2O increases the inhibitory effect of SO2 and NO. Two new reactions are proposed to explain these results, in which SO2 and NO react with Cl2. The consequences of these reactions are a reduction in the oxidative interactions that take place between Hg and Cl2, thus decreasing the amount of Hg oxidation that occurs.